Thickness dependence of anomalous Hall conductivity in L10-FePt thin film - Yu, Jihang; Gonzalez-Hernandez, Rafael; Liu, Liang; Deng, Jinyu; Thong, Herng Yau; Wang, Han; Lin, Weinan; Liu, Hongxi; Poh, Francis; Sinova, Jairo; Chen, Jingsheng (Journal of Physics D: Applied Physics, 2019)
L10 ordered alloys are ideal models for studying the anomalous Hall effect (AHE), which can be used to distinguish the origin from intrinsic (from band structure) or from extrinsic effects (from impurity scatterings). In the bulk limit of L10 ordered FePt films, the AHE is considered to be dominated by the intrinsic contribution, which mainly comes from the strong spin-orbit interaction (SOI) of Pt atoms and exchange-splitting of Fe atoms. The study of anomalous Hall conductivity (AHC) of L10-FePt thin films is of particular interest for its application in spintronic devices. In order to reduce the effects of defects such as grain boundaries, we chose SrTiO3 as the substrate, which has a very small mismatch (0.1%) with L10-FePt films to obtain high quality continuous thin films. We show that the contribution from phonon scattering should be included to fully interpret the AHE signals. For our 6 nm FePt film, the AHE mainly originates from the contribution of phonon scattering. While for the thicker films, the origin for AHE is mainly intrinsic Berry curvature contribution. Both experimental results and calculation results show that AHC increases with thickness and reaches the saturation when the film thickness approaches a critical value.
CRIS-Team Scopus Importer:2023-03-27
Keywords: anomalous Hall effect; L1; spin orbit interaction